The effects of post-emergence weedicides on the Germination, vegetative growth and yield of Tr9 rice variety - Faradila Fathin Eddie (Universiti Malaysia Sabah, 2017)
This study was carried out at the Faculty of Sustainable Agriculture, University Malaysia Sabah (UMS), Sandakan Campus from June 2017 to November 2017 to investigate the effects of post-emergence herbicides which are Roundup (20 ml/10 L of water ha-, 40 ml/10 L of water ha- and 60 ml/10 L of water ha-) and Clincher (20 ml/10 L of water ha-, 30 ml/10 L of water ha-and 40 ml/10 L of water ha-) on the germination, vegetative growth and the yield of TR9 paddy variety. Treatments were arranged as factorial where types of herbicides and the concentration rates are the factors by using Complete Randomized Design (CRD) with three replications. Data collected was analysed using twoway ANOVA at 5% significant level. The result showed for the germination of paddy plants, treatment H2C4 ( 40 ml Clincher/10 L) had highly affected the germination percentage by 32.33%. Treatment H2Cl (0 ml Clincher/10 L) and HlCl (0 ml Roundup/10 L) produced the highest germination index, which were 5.2 and 5.31 respectively. Treatment H2Cl (0 ml Clincher/10 L) and HlCl (0 ml Roundup/10 L) produced the longest root length, which were 5.62 cm and 5.78 cm respectively. Treatment HlCl (0 ml Roundup/10 L) and H2Cl (0 ml Clincher/10 L) produced the lowest percentage of abnormal seedlings, which were 4.33% and 6.44% respectively. For vegetative growth of paddy plants, treatment HlCl (0 ml Roundup/10 L) and H2Cl (0 ml Clincher/10 L) produced the highest number of tiller, which were 19 and 21 respectively. Treatment HlCl (0 ml Roundup/10 L) and H2Cl (0 ml Clincher/10 L) produced the highest culm height of paddy plant at week 16, which were 89.68 cm and 89.99 cm respectively. Treatment H2Cl (0 ml Clincher/10 L) and HlCl (0 ml Roundup/10 L) produced the highest plant height, which were 108.35 cm and 109.51 cm respectively. For yield component, treatment HlCl (0 ml Roundup/10 L) and H2Cl (0 ml Clincher/lOL) produced the highest number of panicle per hill, which were 20 and 21 respectively. Treatment HlCl (0 ml Roundup/lOL) and H2Cl (0 ml Clincher/lOL) produced the longest panicle length, which were 19.72 cm and 19.90 respectively. Treatment HlCl (0 ml Roundup/10 L) and H2Cl (0 ml Clincher/10 L) produced the highest weight of 1000 grains of paddy, which were 26.74 g and 26.78 g respectively. Treatment HlCl (0 ml Roundup/10 L) and H2Cl (0 ml Clincher/10 L) produced the highest number of spikelet per panicle, which were 78 and 86 spikelets per panicle, respectively. Thus, it can be recommended that the control treatment is the best rate to be recommended to the farmer because it has the highest yield among all treatments.